Improving The Quality Of Catchment Area Model Public Services Based On Governance 4.0 - Ratnawati, Susi; Indawati, Indawati; Indarto, Kus (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2024)
This research is to examine Public Service Improvement using the Cathcment Area model based on governance 4.0.Â  The implementation of e-government has experienced challenges since the growth of the industrial era 4.0. The development of technology is so rapid and unstoppable. Digitalisation is starting to enter the cracks of our daily lives. The Catchment Area perspective in this study is an important factor to see the efficiency and effectiveness of services to the community in local government administration based on governance 4.0. The research locus is Sidoarjo Regency. This research uses a qualitative approach. Research focus (1). Identifying factors that affect service quality. Research Results: factors that can affect the catchment area include the function of the region on the condition of the regional economy and also the national economy which is unique in nature, tax sources that can be explored potentially and in real terms to be able to achieve balance between various regions, the efficiency and effectiveness of services to the community in an area that is seen based on the optimal area for the service itself, participation that can be achieved effectively and mutual supervision between citizens and local bureaucracy.Â  Â